1994
DOI: 10.1128/jb.176.5.1413-1421.1994
|View full text |Cite
|
Sign up to set email alerts
|

Structural differentiation of the Bacillus subtilis 168 cell wall

Abstract: Exponential-growth-phase cultures of BaciUus subtilis 168 were probed with polycationized ferritin (PCF) or concanavalin A (localized by the addition of horseradish peroxidase conjugated to colloidal gold) to distinguish surface anionic sites and teichoic acid polymers, respectively. Isolated cell walls, lysozyme-digested cell walls, and cell walls treated with mild alkali to remove teichoic acid were also treated with PCF. After labelling, whole cells and walls were processed for electron microscopy by freeze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 30 publications
6
85
0
Order By: Relevance
“…For instance, autoradiography and fluorescence microscopy (Mobley e t al., 1984), electron microscopy (Clarke-Sturman et al, 1989), freeze-substitution (Graham & Beveridge, 1994) and endolysin susceptibility of the cell wall (Fan et al, 1972) have all suggested a metabolic and/or a qualitative difference between cylinder and septum cell wall which, among other factors, may be due to a difference at the level of teichoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, autoradiography and fluorescence microscopy (Mobley e t al., 1984), electron microscopy (Clarke-Sturman et al, 1989), freeze-substitution (Graham & Beveridge, 1994) and endolysin susceptibility of the cell wall (Fan et al, 1972) have all suggested a metabolic and/or a qualitative difference between cylinder and septum cell wall which, among other factors, may be due to a difference at the level of teichoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Serological studies of Lactobacillus have shown that these species can be assigned to several groups on the basis of specific antigenic characteristics, including production of cell wall polysaccharides, cell wall teichoic acids, and membrane teichoic acids (Knox and Wicken, 1973;Sharpe, 1981). Teichoic acids are components of the outer layers of Gram-positive bacteria; they function like extracellular polysaccharides in processes such as antigen activity, adhesion, and biofilm formation (Birdsell et al, 1975;Doyle et al, 1975;Graham and Beveridge, 1994;Knox and Wicken, 1973;Neuhaus and Baddiley, 2003).…”
Section: Fig 1 Survival Curves Of Enterococcus and Streptococcusmentioning
confidence: 99%
“…bacteria (such as Bacillzls snbtilis) possessed thick amorphous cell walls overlying the plasma membrane (Beveridge,198l), although more recent work using cryo-electron microscopy has now shown these envelopes to be more complex (Beveridge & Graham, 1991 ;Graham & Beveridge, 1994). The staining response for eubacteria has usually been clear-cut with few exceptions (Beveridge & Davies, 1983 ;Beveridge, 1990).…”
Section: T J B E V E R I D G E a N D S S C H U L T Z E -L A Mmentioning
confidence: 99%